Rationale and design of the 2 by 2 factorial design GnG-trial: a randomized phase-III study to compare two schedules of gemtuzumab ozogamicin as adjunct to intensive induction therapy and to compare double-blinded intensive postremission therapy with or without glasdegib in older patients with newly diagnosed AML - Jaramillo Segura, Sonia; Krisam, Johannes; Le Cornet, Lucian; Kratzmann, Markus; Baumann, Lukas; Sauer, Tim; Crysandt, Martina; Rank, Andreas; Behringer, Dirk; Teichmann, Lino; Görner, Martin; Trappe, Ralf-Ulrich; et al. (Trials, 2021)
Overall survival remains poor in older patients with acute myeloid leukemia (AML) with less than 10% being alive after 5 years. In recent studies, a significant improvement in event-free, relapse-free and overall survival was shown by adding gemtuzumab ozogamicin (GO), a humanized antibody-drug conjugate directed against CD33, to intensive induction therapy once or in a sequential dosing schedule. Glasdegib, the small-molecule inhibitor of smoothened (SMO), also showed improved overall survival in patients not eligible for intensive chemotherapy when combined with low-dose cytarabine compared to low-dose cytarabine alone. These findings warrant further investigations in the phase III GnG trial.